Avaliação da composição iônica e aplicação de um índice de qualidade ambiental para a água de irrigação no Baixo-Açu, RN - Antas, Francisco Pio de Souza (2011)
Continental water bodies are used in Brazil and over the world as available resources for society, having ecological, economical and social meanings. However, water resources have been modified by human actions lately, which results in bad water quality and availability. Therefore, there has been an increasing necessity of monitoring the alterations in water quality not to compromise its multiple applications and minimize the negative impacts on environment. This work evaluates the ionic composition, applies an environmental quality rate for irrigation water and monitors the variations of the water caused by human actions. 08 sample sites were chosen from 41km of Rio Açu and 30 samples points from Engenheiro Armando Ribeiro Gonçalves Dam, which is responsible for its perennial process. The samples were analyzed at the Soil and Water Laboratory Analysis of IFRN Campus Ipanguaçu: pH, HCO3-, Na+, K+, Ca2+, Mg2+, Cl-, SO42-, RAS and EC in October and November 2009 and January and February 2010. To evaluate the quality of the water, the patterns proposed by Ayers and Westcot were taken and the measures were done at the referential place (Dam). Then, the water index for irrigation quality was determined through an equation which relates the analyzed variation with the number of characteristics evaluated. The water shows no restriction to be used on irrigation, but for low EC which can leach soluble minerals and might compromise the soil aggregates structure causing infiltration problems. About the quality index, the characteristics which most influence on the index are Cl- and EC, possibly as a result of drainage water from farms of fruitculture in your margin.